Perbedaan Suhu Dan Daya Terima Makanan Berdasarkan Alat Makan Pasien di RSUD DR. SOEGIRI Lamongan - Winiastri, Dinda; Poerbarani, Anggi (Infokes, 2018)
The acceptance is the patient’s acceptance of the food served in a predetermined diet of food waste. The temperature of food and equipment unsed in serving food can affect the appetite of the patient to consume the food.This research was located in RSUD Dr. Soegiri Lamongan. The purpose of this research is to know the difference of temperature and acceptance of food based on the patient’s foodware in RSUD Dr. Soegiri Lamongan. The method used in this research is data collection by Cross Sectional and is kind of observational analytic research. To analyze the differences using Anova and Kruskall Wallis tests. The result provide an overview of the main food temperature based on a plato of 43,3°C, on a hamper of 48,2°C, and at a lunch box of 40,9°C. Vegetable temperature based on plato is 37,8°C, at a hamper of 41,5°C, and at a lunch box of 36,7°C. The temperature of the meat side dish  is based on plato of 42,2°C, on  a hamper 45,2°C, and on lunch box at 40,3°C. Bean side dish temperature based on plato of 33,0°C, at a hamper of 38,0°C, at a lunch box 32,0°C. The food waste of main food based on the plato of 9,0%, 10,5% on the hamper, and 4,0% on the lunch box. The food waste of vegetable based on plato of 14,2%, on the hamper of 20,9%, and on the lunch box of 22,1%. The food waste of meat side dish were based of 9,0% on plato, 7,5% on a hamper, and 12,7% on a lunch box. Then bean side dish based on plato of 10,4%, on the hamper of 17,7%, and on the lunch box of 22,3%. The result of Anova dan Kruskall Wallis statistic test showed that there was difference of food temperature based on the patient’s foodware that is p < 0,1 (main food= 0,000; vegetables = 0,000; meat side dish = 0,000; and bean side dish = 0,000), and there was not difference of acceptance food based on the patient’s foodware that is p > 0,1 (main food= 0,600; vegetables = 0,927; meat side dish = 0,598; and bean side dish = 0,893). Given the use of stainless steel cutlery is more able to maintain food temperature remains warm, it is necessary to consider the use of stainless steel cutlery with a more practical and attractive.